The effect of ankle muscle strength and flexibility on dolphin kick performance in competitive swimmers - Willems, T. M.; Cornelis, J. A. M.; De Deurwaerder, L. E. P.; Roelandt, F.; De Mits, S. (Human Movement Science, 2014)
The velocity of a swimmer is determined by biomechanical and bioenergetics factors. However, little is known about the effect of ankle flexibility on dolphin kick performance. Next to this, scientific evidence is lacking concerning the influence of ankle muscle strength. Therefore, the aim of this study was to investigate the effect of ankle flexibility and muscle strength on dolphin kick performance in competitive swimmers.